NeoApp: Advanced Mathematics Learning Solution for Ordinary Level Students - Suraweera, H; Dissanayaka, M; N. Bandara; Dissanayake, N; Kumari, S (International Journal of Computer Sciences and Engineering, 2022)
The revolution of Information and Communication Technologies (ICT) has enormously impacted the world. E- learning systems are superseding face-to-face learning. According to the 2019 statistics paper by the Sri Lankan ministry of education, the yearly failure rate of an Ordinary Level Mathematics subject is 33.08% which is higher than other subjects. We aim to introduce appropriate and equitable online learning methods for the 13-16 age group where they can build their self-studying abilities with more accurate methods and good confidence. Many students have poor mathematical skills as they do not have accurate and appropriate instructions for their studies. This system will assist students in developing their mathematical knowledge and skills gradually using video tutorials, examples, and tests. When they have a problem or challenging situation, a virtual assistant can help them to solve their difficulties. The proposed virtual tool will help students reduce the boredom they feel while solving mathematical equations or lessons by distracting them with a mathematically based fun game. Some students may not enjoy studying when teachers or parents sit beside them and focus on them. This tool has the ability to make the students keep focused on the lesson without letting them distract from mathematics by making it fun and simple. Therefore, the proposed system utilizes an attention monitoring system to capture student movements and emotions during the learning process. This solution will be highly customizable since it introduces automatic theory and quiz generation.